Pengaruh Trust In A Brand, Brand Awareness Terhadap Brand Loyalty Konsumen Air Mineral Merek Aqua Di Denpasar - Nofita Sari Ndoen; Ni Made Yudhaningsih (Universitas Mahendradatta Denpasar, 2018)
This study was tested on consumers of Aquq brand mineral water in the Denpasar area. Aqua is one of the mineral water brands in the Denpasar area. The purpose of this study was to determine the significance of the influence of trust in a brand, brand awareness on brand loyalty of Aqua brand mineral water consumers partially and simultaneously to brand loyalty of consumers of Aqua brand mineral water in Denpasar. With trust in a brand (X1) and brand awareness (X2) as independent variables and consumer brand loyalty (Y) as the dependent variable. This study uses research instruments in the form of questionnaires with a sample of 100 respondents with population and sample techniques. Data collection also uses the method of observation, literature study and interview. Analysis technique with multiple linear regression test, t-test, F-test and determination of the validity and reliability of the previous test has been done to test the questionnaire items and classical tests have been done for the regression model with SPSSversion 20.0 program.The results of the study stated that independent variables simultaneously have a positive and significant effect on the dependent variable which is evident from the F-test obtained by F-count = 84.82 F-table = 3.09 and 0.00 0.05 and the magnitude of the influence given 62 , 90%. T-test results obtained that the trust in a brand variable (X1) has a positive and significant effect on consumer brand loyalty with a regression coefficient of 0.003 units and is proven by the results of tcount 3,100 t table 1,984 and Sig. t 0.003 0.05. Positive influence is given by brand awareness variable (X2) and has a positive and significant effect on consumer brand loyalty based on t-test that is t-count = 6.980 t-table = 1.984 and Sig. t = 0.003 0.05 and the effect given with the regression coefficient is only 0.801. So that the regression equation is obtained Y = 0.688 + 0.037X1 + 0.801X2. For that the company / company leadership should pay attention to the independent variables together because the influence given will be greater